Waves generated by two or more ships in a channel - Do Nascimento, Maria Francisca; Neves, Claudio F.; De Freitas MacIel, Geraldo [UNESP] (My University, 2010)
The numerical model FUNWAVE+Ship simulates the generation and propagation of ship waves to shore, including phenomena such as refraction, diffraction, currents and breaking of waves. The interaction of two wave trains, generated by ships moving either in the same direction at different speeds or in opposite directions, is studied. Focus is given to the wave orbital velocities and to the free surface pattern.
Keywords: Boussinesq waves; Orbital velocities; Ship waves; Wave refraction; Wave-wave interaction; Boussinesq; Wave-wave interactions; Coastal engineering; Refraction; Ships; Water waves